Gastrointestinal endoscopy in the era of the acute pandemic of coronavirus disease 2019: Recommendations by Japan Gastroenterological Endoscopy Society (Issued on April 9th, 2020). Issue 5 (28th May 2020) - Irisawa, Atsushi; Furuta, Takahisa; Matsumoto, Takayuki; Kawai, Takashi; Inaba, Tomoki; Kanno, Atsushi; Katanuma, Akio; Kawahara, Yoshiro; Matsuda, Koji; Mizukami, Kazuhiro; Otsuka, Takao; Yasuda, Ichiro; et al.
Abstract : All gastrointestinal endoscopic procedures have a high risk of aerosol contamination of the coronavirus disease 2019 (COVID‐19) to endoscopists, nurses, and healthcare assistants. Given the current pandemic situation of COVID‐19, the Japan Gastroenterological Endoscopy Society issued the recommendation for gastrointestinal (GI) endoscopy based on the status of COVID‐19 as of April 9, 2020, in Japan: (i) indications for GI endoscopy in the pandemic of COVID‐19; (ii) practical protective equipment for medical personnel depending on the risk for COVID‐19; (iii) preprocedural management, such as pharyngeal local anesthesia using lidocaine spray which has a potential to generate the aerosols; (iv) ideal settings of the endoscopy room including the numbers of the staff and the patients; (v) postprocedural management, such as undressing and follow‐up of the patients, as well as the involved staff, were documented to fit the practical scenarios in GI endoscopy, with the available data in Japan and the world. We believe that certain measures will prevent further spread of COVID‐19.